Liner shipping connectivity as determinant of trade - Marco Fugazza; Jan Hoffmann (Journal of Shipping and Trade (JST), 2017)
Transport connectivity is a crucial determinant of bilateral exports. This paper presents an empirical assessment of the relationship between bilateral maritime liner shipping connectivity and exports in containerizable goods during the period 2006-2013. Making use of probed 'gravity' type trade models, the paper incorporates new data on different measurements of maritime distance, as well as a unique new dataset and new bilateral connectivity indices developed by UNCTAD. The empirical investigations unequivocally show that lacking a direct maritime connection with a trade partner is associated with lower values of exports; any additional transshipment is associated with a 40% lower value of bilateral exports. Other indicators of liner shipping connectivity incorporated in the research take into consideration levels of competition and container vessel sizes. Results also indicate that the quality of bilateral connectivity as measured by several composite indices is a crucial determinant of bilateral exports. All empirical results suggest that in the absence of a bilateral connectivity indicator the impact of distance on bilateral exports in classical gravity models is likely to be overestimated.
Keywords: 650; Liner shipping bilateral connectivity; Exports of containerizable goods; Container shipping networks; Gravity models